Obstetric anesthesia: Spinal Sub-arachnoid Blockade - Ahmad, Nezamuddin (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
doi: 10.3329/bjog.v23i1.3048 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 1-2